Dampak Implementasi Gerakan Literasi Sekolah pada Sikap Peserta Didik di SD N 1 Pandowan - Susianti, Tri Saptuti; Salimi, Moh; Arsy, Rahma Auliya; Hidayah, Ratna (Universitas Muhammadiyah Magelang, 2021)
This study aims to describe the impact of the school literacy movement on the attitudes of students in Public Elementary School 1 Pandowan. A descriptive qualitative approach was used in this research. The research subjects were aimed at school principals, librarian, teachers and fourth grade students of Public Elementary School 1 Pandowan. The methods used for data collection were interviews, questionnaires, and documentation studies. The data analysis technique uses interactive analysis (data reduction, data presentation, and verification/conclusion). The results of the study prove that the impact of literacy activities on fourth grade students of Public Elementary School 1 Pandowan results in the formation of social, curious, communicative, and fond reading characters through literacy activities that are well established. The literacy program with a variety of activities is a means to shape the character of students so that these findings contribute to the process of directing, guiding, and mentoring students to carry out positive literacy activities and uphold useful values.